Empowering farmers through pineapple processing innovation as featured products of Sidorejo Village - Juwita, Ratna; Manggara, Algafari Bakti; Parwono, Eka Andryanna; Dewanti, Angel Khoirun Nisa; Nisa’, Fauziah Wardatun; Haryono, Norman Yoshi; Pahrany, Andi Daniah (Universitas Muhammadiyah Magelang, 2025)
Farmer groups in Sidorejo Village, Blitar, face significant challenges characterized by the low added value of pineapple harvests and minimal innovation in post-harvest processing, including waste utilization. This community service project aimed to enhance the skills of partner groups in processing pineapple fruit and peel into economically valuable probiotic beverages using fermentation methods packaged attractively. The activity primarily involved the PKK women's group of Sidorejo Village and was conducted in-person. The methodology included education, direct demonstration of product creation, named Pinaboocha (pineapple kombucha) and Pinatepa (pineapple tepache), and packaging mentoring. Post-training evaluation revealed a significant increase in competence while 85% of participants understood the benefits of Pinaboocha and Pinatepa, and 85% expressed interest in developing these beverages into a business. These findings demonstrate that innovating the processing of pineapple fruit and waste through fermentation not only increases product quality but also successfully creates new, sustainable business opportunities based on local potential.